AKSIOLOGI SAINS - Hafizi, Ahmad; Agustari, Jesi; Juliana, Peby; Syarah, Siti; Balitesa, Tiara; Hartati, Yulfi; Harahap, Sahrul Sori Alom (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The purpose of this study was to determine the Axiology of  Science, the use of scientific knowledge, How to Solve Problems, and the Neutrality of Science. The data collection technique used is analysis and evaluation from several related sources while this type of research exists, it is descriptive qualitative. The results of research on the axiology of science can be concluded that the axiology of science is a value and ethics in studying and understanding Natural Sciences in a bound and arranged manner. Furthermore, in the use of scientific knowledge, there are three theories, first theory as a means of explanation, second theory as a means of fortune telling, and finally theory as a controlling tool. Then the results of research on the way science solves problems can be found that there are three steps in solving problems, first identifying problems, second looking for theories, third reading the literature again and establishing actions. And the neutralization of science can be found that whether or not science is neutral depends on its use and purpose